Edge Computing through Virtual Force for Detecting Trustworthy Values - R.Dhaya,; R.Kanthavel, (IRO Journal on Sustainable Wireless Systems, 2020)
As the advancement of IoT (Internet of Things) and other emerging mobile application continues, it is an accepted fact that Edge Computing paradigm is considered to be the best fit in terms of fulfilling the resource requirements. Moreover, it is a fact that the data collected by the sensor networks serves as the base for the IoT applications as well as the systems. However, due to advancement in cybercrimes, there is a possibility that the data collected through the sensor networks are vulnerable to attacks which may result in serious consequences. The proposed work focuses on a new model which is used to gather trustworthy data using edge computing in IoT. In order to get the accurately quantified trust values, the sensor nodes are analyzed and found from different dimensions. Moreover, with the help of trust value obtained, it is possible to find the best mobility path which carries the highest value of trust. This data is gathered from the sensors with the help of mobile edge data collector. This analysis shows that for a trustworthy data collection model of IoT, there is noticeable improvement in terms of energy conservation and system security, thereby improving the performance of the system.
Keywords: Internet of Things; Edge Computing; Quantified trust values; Sensor Nodes